2013
DOI: 10.1021/es400659b
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Efficient Removal of Microcystins by Ordered Mesoporous Silica

Abstract: To alleviate the environmental and health threats from water resources polluted by large-sized microcystins (MCs), we demonstrate for the first time that ordered mesoporous silica materials with large pore sizes of 2-12 nm can be used as adsorbents for rapid and efficient removal of MCs. The obvious correlations between adsorption performance of MCs and physicochemical properties of adsorbents including pore mesostructure, texture and size, and surface chemistry have been well established. Accordingly, an exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 51 publications
0
69
0
1
Order By: Relevance
“…It was reported that MCM-41 displayed a quite short equilibrium time (even less than 1 min) to reach its maximum capacity for nitrobenzene adsorption [3], which is crucial for its practical application. Similarly, quick equilibrium was also observed for other organic pollutants adsorption such as pharmaceuticals [5], microcystins [6] using ordered mesoporous silica adsorbents. However, MCM-41 has a relatively low adsorption capacity for the removal of nitrobenzene.…”
Section: Introductionmentioning
confidence: 58%
“…It was reported that MCM-41 displayed a quite short equilibrium time (even less than 1 min) to reach its maximum capacity for nitrobenzene adsorption [3], which is crucial for its practical application. Similarly, quick equilibrium was also observed for other organic pollutants adsorption such as pharmaceuticals [5], microcystins [6] using ordered mesoporous silica adsorbents. However, MCM-41 has a relatively low adsorption capacity for the removal of nitrobenzene.…”
Section: Introductionmentioning
confidence: 58%
“…33 The IEP value shifts toward higher pH values of approximately 4.5 in the presence of the nitrogen-containing functional group (8.5ODDMA-MP) due to the inherent electropositive nature of quaternary ammonium salts. 34 With a further increase in nitrogen content, the samples exhibit increased IEP values of 4.8 and 5.3 for 11.5ODDMA-MP and 13ODDMA-MP, respectively.…”
mentioning
confidence: 93%
“…By contrast, BC-300 exhibits low carbon content (70.1 %), high H/C ratio (0.617), and low specific surface area (only 4.1 m 2 g −1 ), indicating that some wood organic residues remain on the structure of BC-300 after incomplete carbonization ). The three-dimensional size of MCLR was reported as 1.9 nm×1.5 nm×1.1 nm (Teng et al 2013). Therefore, the micropore regions (pore size <2 nm) may be unavailable for MCLR adsorption because the second widest dimension of MCLR (1.7× 1.5=2.55 nm) is 1.7 times larger than 2 nm (Xiao et al 2012).…”
Section: Characterization Of Biocharsmentioning
confidence: 99%